Peningkatan Aktivitas dan Prestasi Belajar IPAS Materi Kekayaan Budaya Indonesia Melalui Circ Kelas 4 Sekolah Dasar - Moch. Lutkhi Azhari; Octarina Hidayatus S; Endang Suprihatin (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to improve learning activities and achievement in science and technology on Indonesian Cultural Wealth material through the Cooperative Integrated Reading and Composition (CIRC) learning model in grade 4 of elementary school. This research uses a Classroom Action Research (PTK) approach with a two-cycle system. This research was conducted on grade 4 students at SDN Bantengan 01, Wungu District, Madiun Regency. Research data was collected through observation and tests. Data analysis was carried out using a descriptive approach that focused on students' learning activities and achievements, as well as the learning implementation process. The research results showed that students' science and science learning achievement increased in the percentage of classical learning completion from 30.76% (4 out of 13 students) in the initial test to 84.61% (11 out of 13 students) in Cycle II. The percentage of learning completeness (classical) in Cycle II has met the predetermined target, namely 80% of all students achieved a score ≥ 70 (complete learning). Student activity in learning has also increased. This is evidenced by the increase in the percentage of classically active students from 30.76% (4 out of 13 students) in Cycle I to 76.92% (10 out of 13 students) in Cycle II. The percentage of classical student activity in Cycle II has met the specified target, namely ≥ 70%.